STUDY OF MULTIPLE ENTRY OF ADOLESCENT STUDENTS STUDYING IN UNDERGRADUATE COLLEGES: IN THE CONTEXT OF NATIONAL EDUCATION POLICY 2020 - Rawat, Devki; Singh, Bindu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The National Education Policy 2020 is a revolutionary step towards bringing about a comprehensive reform in the educational structure of India. This policy emphasizes on making higher education more flexible and inclusive by implementing multiple-entry and multiple-exit system. In the context of this policy, it is very important to study multiple entry of adolescent students studying in undergraduate colleges, as it not only makes their educational journey more convenient but also empowers their skill development and career building. The multiple entry system allows students to continue their education or stop at a specific stage according to their personal, economic, and social needs. Under this system, students can complete their undergraduate education at different levels within one to four years. For example, there is a provision to get a certificate after completing one year of study, a diploma after two years, a bachelor's degree after three years, and a bachelor's degree with research work in four years. This will benefit students who are forced to leave their studies for some reason, as they can resume their studies from the same level where they left. This system can prove to be extremely beneficial for adolescent students in colleges, as many students of this age group are unable to continue their studies due to financial difficulties, personal responsibilities, or other reasons. The multiple entry system provides them an opportunity to re-engage in education, so that they can achieve their goals without any educational disruption. This flexibility also allows students to balance their education with various skill courses and employment opportunities. The concept of academic credit bank has also been introduced to make the multiple entry system effective under the National Education Policy 2020. It is a digital database in which the credits earned by the students are stored and they can resume their education by using them when needed. This initiative provides flexibility and diversity to the students in different subjects, so that they can choose courses according to their interest and career requirements. It is clear from this study that the multiple-entry system not only provides a golden opportunity to adolescent students to complete their education, but also helps them to become self-reliant. This policy eliminates the rigidity of the traditional education system and makes it more inclusive and flexible, so that students can get education according to their ability. Findings obtained from the research study - No significant difference was found on the basis of gender in the multiple entry of adolescent students studying in graduate level colleges of Bijnor district, No significant difference was found on the basis of regional in the multiple entry of adolescent students studying in graduate level colleges of Bijnor district.